Hover Widgets: Using the Tracking State to Extend the Capabilities of Pen-Operated Devices - Grossman, Tovi; Hinckley, Ken; Baudisch, Patrick; Agrawala, Maneesh; Balakrishnan, Ravin (CHI '06 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2006)
We present Hover Widgets, a new technique for increasing the capabilities of pen-based interfaces. Hover Widgets are implemented by using the pen movements above the display surface, in the tracking state. Short gestures while hovering, followed by a pen down, access the Hover Widgets, which can be used to activate localized interface widgets. By using the tracking state movements, Hover Widgets create a new command layer which is clearly distinct from the input layer of a pen interface. In a formal experiment Hover Widgets were found to be faster than a more traditional command activation technique, and also reduced errors due to divided attention.